Purity in the gospel of John: early Jewish tradition, Christology, and ethics - Rogan, Wil (Library of New Testament studies, 2023)
"Wil Rogan focuses on how the Fourth Gospel adapts biblical and early Jewish traditions of purity related to divine revelation and Israel's restoration to its Christology, soteriology, and ethics"--